Effective site investigation - Clayton, C.R.I (Site investigation in construction series, 2013)
Effective Site Investigation provides an introductory guide to accepted best practice for site investigations, both for construction professionals such as civil and structural engineers, builders and architects, and for their clients. It has been prepared by the Site Investigation Steering Group, a multidisciplinary body representing those professional institutions, learned societies, trade organisations and government agencies involved or affected by site investigations. The second edition represents a major revision and extension of the series with the aim of bringing together the whole site investigation industry and is intended for general application to all ground investigation work.